Aplikasi Teknologi PETIS Berbasis Solar Panel di Desa Sinarancang Kecamatan Mundu Kabupaten Cirebon - Rindi Wulandari; Taryo; Nurdiyanto; Nunu Nugraha (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
BUMDes Rancang Jaya has several activities such as a cafe business unit, village water management business unit, agricultural product management business unit, handicraft and industrial business unit. On agricultural land, there are several obstacles, one of which is the lack of resources to manage agricultural land. Automating plantation irrigation activities can change the paradigm from a manual and static system to a more dynamic system that leads to increased water use efficiency and leads to higher production yields. Application of solar panel-based PETIS Technology applications to increase the efficiency and effectiveness of farmers in managing their crops. Especially in surface water utilization systems as irrigation water and in the consistency of giving water to plants because PETIS Technology uses the RTC system, which is automatic watering based on the desired time based on solar panels. The method used is advocacy. Starting with conducting surveys and observations to analyze partner problems, assembling and testing tools, installing tools, and providing community assistance. Solar panel-based PETIS technology can be utilized for an automatic watering system on agricultural land in Sinarancang Village, which has a high level of efficiency because the electricity comes from solar panels that are free of charge.